Structural identification and antitumor activity of the extracellular polysaccharide from Aspergillus terreus. Issue 10 (October 2016) - Li, Hongyan; Gao, Tong; Wang, Jingchen; Tian, Shasha; Yuan, Xin; Zhu, Huajie
Graphical abstract: Highlights: The exopolysaccharide AP2A was isolated from the fungus Aspergillus terreus . The structure of AP2A was investigated by NMR and chemical methods. AP2A could arrest HeLa cells in G2/M phase and induce HeLa cells apoptosis. Abstract: A water-soluble extracellular polysaccharide, AP2A, was purified from the culture medium of Aspergillus terreus . AP2A was mainly composed of mannose with the average molecular weight of about 30.3 kDa. By chemical, IR, GC/MS, 1D and 2D NMR spectroscopic analysis, the backbone of AP2A was found to be composed of [→3)-α-d -Man p (1→], [→6)-α-d -Man p (1→] and [→2, 6)-α-d -Man p (1→] with [α-d -Man p -(1 → 2)-α-d -Man p (1→] and [α-d -Man p -(1→] as branches substituted at the C-2 position of [→2, 6)-α-d -Man p (1→]. AP2A showed an anti-proliferative effect in vitro on HeLa and MCF-7 cells in a dose- and time-dependent manner. Flow cytometry showed that AP2A inhibited HeLa cell proliferation by arresting cell cycle in G2/M phase, and Annexin V-FITC/PI double staining assay indicated that AP2A could also induce HeLa cells apoptosis. These results suggest that the extracellular polysaccharide, AP2A from Aspergillus terreus, has possible chemotherapeutic applications.